2020
DOI: 10.1002/oby.22769
|View full text |Cite
|
Sign up to set email alerts
|

Weight Change 2 Years After Termination of the Intensive Lifestyle Intervention in the Look AHEAD Study

Abstract: Objective: This study evaluated weight changes after cessation of the 10-year intensive lifestyle intervention (ILI) in the Look AHEAD (Action for Health in Diabetes) study. It was hypothesized that ILI participants would be more likely to gain weight during the 2-year observational period following termination of weight-loss-maintenance counseling than would participants in the diabetes support and education (DSE) control group. Methods: Look AHEAD was a randomized controlled trial that compared the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 36 publications
2
7
0
1
Order By: Relevance
“…Under a 5-year weight regain assumption, Look AHEAD is borderline cost-effective, but the ICER decreases when assuming a linear regain trend over time. The latter may be more appropriate and in line with recently published Look AHEAD data showing that in the 2 years after cessation of the intervention, there was no evidence of any weight regain, improving the case for cost-effectiveness further [ 30 ].…”
Section: Discussionmentioning
confidence: 56%
“…Under a 5-year weight regain assumption, Look AHEAD is borderline cost-effective, but the ICER decreases when assuming a linear regain trend over time. The latter may be more appropriate and in line with recently published Look AHEAD data showing that in the 2 years after cessation of the intervention, there was no evidence of any weight regain, improving the case for cost-effectiveness further [ 30 ].…”
Section: Discussionmentioning
confidence: 56%
“…Several studies have shown that while some weight is often regained in the period after intensive weight loss interventions for adults with obesity, participants typically remain below baseline weight, though these findings have been chiefly in younger adults. 7,8 Our overall weight maintenance findings align with those previously published for older adults. 9 Our findings offer encouraging evidence that technology-based interventions may address access disparities and allow for maintained weight loss for older adults in rural areas.…”
Section: Discussionsupporting
confidence: 90%
“…This was true for both those who significantly responded to the initial intervention and those who did not. Several studies have shown that while some weight is often regained in the period after intensive weight loss interventions for adults with obesity, participants typically remain below baseline weight, though these findings have been chiefly in younger adults 7,8 . Our overall weight maintenance findings align with those previously published for older adults 9 .…”
Section: Discussionsupporting
confidence: 86%
“…We found similar associations of ILI with weight and HbA 1c for the linked sample compared with the full Look AHEAD study during and after the trial (Figure 2). During our sample period from 2012 to 2015, the linked ILI group continued to have lower weight than the control group (adjusted difference: −1.9% [95% CI, −2.6% to −1.2%] of initial body weight; P < .001). However, there was no significant difference in HbA 1c between 2012 and 2015.…”
Section: Resultsmentioning
confidence: 86%
“…We found similar associations of ILI with weight and HbA 1c for the linked sample compared with the full Look AHEAD study during and after the trial (Figure 2). 26 ; P = .89). We also estimated year-specific ILI vs control group differences in the probability of hospital admission and ED visits, Part D prescription drug costs, and total Medicare spending.…”
Section: Associations Of Ili With Weight and Hba 1c During And After mentioning
confidence: 90%